Covenantal Pluralism: Resonances and Dissonances in Cambodia. Issue 1 (2nd January 2022) - Kent, Alexandra
Abstract : This article explores to what extent the ideals of covenantal pluralism resonate with or deviate from socio-cultural processes in Cambodia. It examines efforts made by various Khmer Buddhist protagonists to recover moral order following the Khmer Rouge era. Conversely, it describes how power continues to be monopolized by certain actors in a way that undermines trust in institutions and in other people generally. Thus it explores the tension between a religious system that might offer protection for all and a predatory political reality marked by unrestrained greed that benefits the powerful at the expense of the vulnerable.